The transcription factor Dach1 is essential for podocyte function - Endlich, Nicole; Kliewe, Felix; Kindt, Frances; Schmidt, Katharina; Kotb, Ahmedm.; Artelt, Nadine; Lindenmeyer, Maja T.; Cohen, Clemens D.; Doering, Franziska; Kuss, Andreas W.; Amann, Kerstin Ute; Moeller, Marcus J.; et al. (Journal of Cellular and Molecular Medicine, 2018)
Dedifferentiation and loss of podocytes are the major cause of chronic kidney disease. Dach1, a transcription factor that is essential for cell fate, was found in genome-wide association studies to be associated with the glomerular filtration rate. We found that podocytes express high levels of Dach1 in vivo and to a much lower extent in vitro. Parietal epithelial cells (PECs) that are still under debate to be a type of progenitor cell for podocytes expressed Dach1 only at low levels. The transfection of PECs with a plasmid encoding for Dach1 induced the expression of synaptopodin, a podocyte-specific protein, demonstrated by immunocytochemistry and Western blot. Furthermore, synaptopodin was located along actin fibres in a punctate pattern in Dach1-expressing PECs comparable with differentiated podocytes. Moreover, dedifferentiating podocytes of isolated glomeruli showed a significant reduction in the expression of Dach1 together with synaptopodin after 9 days in cell culture. To study the role of Dach1 in vivo, we used the zebrafish larva as an animal model. Knockdown of the zebrafish ortholog Dachd by morpholino injection into fertilized eggs resulted in a severe renal phenotype. The glomeruli of the zebrafish larvae showed morphological changes of the glomerulus accompanied by down-regulation of nephrin and leakage of the filtration barrier. Interestingly, glomeruli of biopsies from patients suffering from diabetic nephropathy showed also a significant reduction of Dach1 and synaptopodin in contrast to control biopsies. Taken together, Dach1 is a transcription factor that is important for podocyte differentiation and proper kidney function.
EVALuna2:34433